VulnScan Suite: Uma Ferramenta Integrada para Análise Automatizada de Vulnerabilidades em Redes Locais - Frazão, Carlos Gabriel de Oliveira; Lins, Theo Silva (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This paper presents VulnScan Suite, an integrated tool developed in Python for automated vulnerability analysis in local networks. The tool orchestrates multiple cybersecurity tools, including Nmap, Nikto, Dirb, TestSSL, Enum4linux, SearchSploit, and SNMP Scanner, providing a unified approach for security audits. The system implements automatic host discovery, parallel scan execution, and report generation in multiple formats. Experimental tests demonstrated the tool’s capability to identify 910 vulnerabilities in a single host, with optimized execution time through parallelization, resulting in 67% improvement compared to manual execution of the same tools. The tool aims to facilitate the work of security professionals and serve as an educational platform for cybersecurity students, being distributed under MIT license for maximum accessibility.